2021
DOI: 10.1177/09691413211009940
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with test failure in pregnant women undergoing cell-free DNA-based testing for fetal trisomy

Abstract: Objective To investigate the factors associated with cell-free DNA test failure, and the optimal subsequent management of these pregnancies. Methods This was a retrospective study of 27,363 singleton pregnancies undergoing cell-free DNA testing. Women with cell-free DNA test failure were divided into a high-risk group and a low-risk group according to their indications. The subsequent management and pregnancy outcomes of these women were followed up. Results The rate of cell-free DNA test failure at the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 29 publications
0
7
1
Order By: Relevance
“…The no-call rates of the cfDNA tests were assessed by various technologies, and methods based on MPS were subtotaled to have the lowest no-call rate (1.58%) [ 5 ]. The no-call rate in our center based on the MPS platform was 1.12% (111/9871), which is lower than that in previous studies [ 5 , 8 , 13 , 14 ]. The most important reason is that the no-call rate in the current study was calculated based on whether a result was obtained after sequencing, and problems of previous processes, including sampling, delivery, tracking, and plasma preparation, were not considered.…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…The no-call rates of the cfDNA tests were assessed by various technologies, and methods based on MPS were subtotaled to have the lowest no-call rate (1.58%) [ 5 ]. The no-call rate in our center based on the MPS platform was 1.12% (111/9871), which is lower than that in previous studies [ 5 , 8 , 13 , 14 ]. The most important reason is that the no-call rate in the current study was calculated based on whether a result was obtained after sequencing, and problems of previous processes, including sampling, delivery, tracking, and plasma preparation, were not considered.…”
Section: Discussioncontrasting
confidence: 66%
“…The primary cause of no-call test results in the current study was data fluctuation, mainly due to sample degradation, library preparation, and other technical reasons. However, previous studies have demonstrated that the most common reason for no-call test results is low FFs [ 7 , 8 ]. Different definitions of test failure or no-call test results should be considered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Providers are encouraged to contact the laboratory directly with questions about uncertain results and request information from the medical team to assist with interpretation or clarification 13 . Atypical results can occur for a number of reasons (ie, low fetal fraction, laboratory processing issues), some of which may be rectified with a new blood sample 32 . When maternal malignancy is suspected, repeat cfDNA screening is not recommended.…”
Section: Genetic Counseling For Atypical Cfdna Results Indicative Of ...mentioning
confidence: 99%
“…13 Atypical results can occur for a number of reasons (ie, low fetal fraction, laboratory processing issues), some of which may be rectified with a new blood sample. 32 When maternal malignancy is suspected, repeat cfDNA screening is not recommended. If it is unclear from the laboratory report whether maternal malignancy should be considered, a laboratory counselor or laboratory director can be contacted for clarification.…”
Section: Indicative Of Maternal Malignancymentioning
confidence: 99%